The Effect of the Teams Games Tournament Type Cooperative Learning Model on Science Learning Outcomes - Efendi, Raimon; Anggrayni, Melisa; Atlia (The Future of Education Journal, 2025)
This study aims to determine the effect of the cooperative learning model of the Teams Games Tournament (TGT) type on science and social studies (IPAS) learning outcomes. This research uses the cooperative learning model of the Teams Games Tournament (TGT) type, which is one of the most suitable methods to be used as a learning aid in IPAS. The model consists of five stages: class presentation, team formation, games, tournament, and team recognition. The results of the study show that the cooperative learning media of the Teams Games Tournament type led to an average difference of 9.17 points between the pretest and posttest scores, with an average posttest score of 69.6 and a pretest score of 55.6. This difference is statistically significant, as supported by the results of the paired sample t-test. The analysis shows that the significance value (2-tailed) is .005 (< 0.05), indicating a significant difference between the pretest and posttest scores. Based on the results, the TGT learning model has a significant effect on learning outcomes in the theme My Wealthy Indonesia (Indonesiaku Kaya Raya) for IPAS subject content. This research employed a quantitative experimental method with data collection techniques including observation and documentation. The findings suggest that the TGT media can be a viable alternative.